Κ. Χατζόπουλος, Σπ. Πασαγιάννης και άλλοι - Χάρης, Πέτρος, 1902-1998 (Βασική βιβλιοθήκη / Αετός, 1955)
Κώστας Παρορίτης -- Δημήτριος Χατζόπουλος -- Δημήτριος Π. Ταγκόπουλος -- Κώστας Πασαγιάννης -- Πάνος Δ. Ταγκόπουλος